Genotype × environment interaction of quality protein maize grain yield in Nepal - Shrestha, Jiban; Kunwar, Chitra Bahadur; Upadhyaya, Jharana; Giri, Maiya; Katuwal, Ram Bahadur; Acharya, Ramesh; Gurung, Suk Bahadur; Adhikari, Bhim Nath; Paudel, Amrit Prasad; Paneru, Ram Babu (Journal of Maize Research and Development, 2016)
In order to determine G × E interaction of quality protein maize grain yield, six maize genotypes were evaluated under different environments of three Terai (Chitwan, Surkhet and Doti) and four mid hill (Dhankuta, Lalitpur, Dolakha and Kaski) districts of Nepal during summer seasons of 2014 and 2015. The experiments were conducted using randomized complete block design along with three replications. The genotypes namely S99TLYQ-B, S99TLYQ-HG-AB and S03TLYQ-AB-01 were identified high yielding and better adapted genotypes for Terai environments with grain yield of 4199 kg ha-1, 3715 kg ha-1, and 3336 kg ha-1 respectively and S99TLYQ-B and S03TLYQ-AB-01 for mid hill environments with grain yield of 4547 kg ha-1 and 4365 kg ha-1 respectively. Therefore, these genotypes can be suggested for cultivation in their respective environments in the country.